Robbins and Cotran pathologic basis of disease / Vinay Kumar - Kumar, Vinay
The cell as a unit of health and disease -- Cellular responses to stress and toxic insults: adaptation, injury, and death -- Inflammation and repair -- Hemodynamic disorders, thromboembolic disease, and shock -- Genetic disorders -- Diseases of the immune system -- Neoplasia -- Infectious diseases -- Environmental and nutritional diseases -- Diseases of infancy and childhood -- Blood vessels -- The heart -- Diseases of white blood cells, lymph nodes, spleen, and thymus -- Red blood cell and bleeding disorders -- The lung -- Head and neck -- The gastrointestional tract -- Liver and gallbladder -- The pancreas -- The kidney -- The lower urinary tract and male genital system -- The female genital tract -- The breast -- The endocrine system -- The skin -- Bones, joints, and soft tissue tumors -- Peripheral nerves and skeletal muscles -- The central nervous system -- The eye